A code reuse method for many-core coarse-grained reconfigurable architecture function library development - Shuo Li; Guo Chen; Hemani, A. (2011 International Symposium on Integrated Circuits, 2011)
In this paper 1 , a code reuse method is proposed to enhance the efficiency of the function library development of many core coarse-grained reconfigurable architecture. The method focuses on developing and using the precompiled ReCon-figurable Functions (RCFs) in the function library. By applying this method on the RCF development, functions are objectified like classes in any objective-oriented programming language. Using a function is to instantiate a selected RCF. Similar functions can be instantiated from the same RCF. Thus, the total number of RCFs to be compiled is reduced and the global programming efficiency is increased and the labor requirement for application development is reduced.